URGENSI PEMBELAJARAN KONTEKSTUAL PENDIDIKAN PANCASILA BERBASIS KEARIFAN LOKAL MINANGKABAU DI SEKOLAH DASAR - Hendrizal Hendrizal; Pebriyenni Pebriyenni; Darwianis Darwianis; Endut Ahadiat (Study program PGSD FKIP Universitas Bung Hatta, 2026)
This study aims to critically explore the urgency of contextual Pancasila Education learning based on Minangkabau local wisdom in elementary schools as an effort to strengthen the internalization of Pancasila values, character development, and students’ civic competencies. Employing a qualitative approach through literature analysis, this study examines various academic sources, including reputable international journal articles, accredited national journals, scholarly books, and international conference proceedings related to contextual learning, Pancasila Education, citizenship education, and Minangkabau local wisdom. Data were analyzed through identification, classification, synthesis, and critical interpretation of relevant literature to obtain a comprehensive understanding of the relationship among Pancasila values, contextual learning approaches, and Minangkabau local wisdom. The findings indicate that Pancasila Education in elementary schools continues to face challenges, particularly the dominance of text-oriented instruction and the limited connection between learning materials and students’ real-life experiences. Minangkabau local wisdom, reflected in the philosophy of Adat Basandi Syarak, Syarak Basandi Kitabullah, deliberative traditions, mutual cooperation, and the principle of alam takambang jadi guru, demonstrates strong relevance to Pancasila values and therefore has significant potential as an authentic learning resource within contextual learning. Furthermore, this study proposes a conceptual learning model integrating Pancasila values, Minangkabau local wisdom, and the Contextual Teaching and Learning approach to support the development of the Pancasila Student Profile in elementary schools.